Attitude Detection and Localization for Unmanned Aerial Vehicles. Issue 4 (1st October 2016) - Jean, Jong-Hann; Liu, Bo-Syun; Chang, Po-Zong; Kuo, Li-Chuan
Abstract: Over the past decade, unmanned aerial vehicles (UAV) have been developed rapidly for more and more applications among civilian uses such as reconnaissance, earth sensing, and scientific data collection. For achieving those applications, the UAVs have to be equipped with an accurate attitude detection and localization module to maintain a stable attitude and a correct heading direction during flight. This paper reports the implementation of an attitude detection and localization module for UAVs by integrating sensing data from the GPS sensor, inertial measurement unit (IMU), and digital compass. The module is realized based on the Arduino platform to compute the fused attitude and localization information and send the fused data to the ground station computer in real time. To avoid the data drift problem of the GPS sensor, the zero velocity updated algorithm is used to detect the zero motion of the vehicle from IMU measurements for deciding whether to update the localization information. Graphical abstract: System architecture of the attitude detection and localization module, in which the Arduino microcontroller is utilized to read measurements from IMU to calculate the acceleration and attitude of the UAV, read data from the digital compass to obtain flight direction, and retrieve the GPS packets to get latitude and longitude. Then, the XBEE transceiver is used to send these integrated attitude and localization data to the ground station computer for further processing.